2021
DOI: 10.1002/cjoc.202000334
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Carbonized Polymer Dots at the Nano‐Bio Interface and Their Luminescent Mechanism: A Physical Chemistry Perspective

Abstract: Carbonized polymer dots (CPDs) have been widely applied in biomedical fields, such as imaging, diagnosis and drug delivery. Since the complex, non‐equilibrated and dynamic nature of biological systems inevitably affect the predesigned properties of CPDs, then efficiency and ultimate outcome of CPDs in biological identity will be transformed by the ubiquitous nano‐bio interactions. Herein, our recent progress about elucidating the behavior of CPDs at nano‐bio interface from the perspective of physical chemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Figure b shows the high-resolution C 1s spectrum and three separate peaks corresponding to carbonyl carbons (CO, 287.8 eV), sp 2 carbons (CC, 284.6 eV), and sp 3 carbons (C–O/C–N, 286.1 eV) Figure c shows a high-resolution N 1s spectrum with two peaks, corresponding to pyrrolic N (400.2 eV) and pyridinic N (399.1 eV), respectively. , Figure d shows that the O 1s band contains two peaks at 533.0 and 531.6 eV corresponding to C–O and CO, respectively. , From the XPS results, it was found that the hydroxyl (−OH) and amino (−NH 2 ) groups exist on the surface of CPDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure b shows the high-resolution C 1s spectrum and three separate peaks corresponding to carbonyl carbons (CO, 287.8 eV), sp 2 carbons (CC, 284.6 eV), and sp 3 carbons (C–O/C–N, 286.1 eV) Figure c shows a high-resolution N 1s spectrum with two peaks, corresponding to pyrrolic N (400.2 eV) and pyridinic N (399.1 eV), respectively. , Figure d shows that the O 1s band contains two peaks at 533.0 and 531.6 eV corresponding to C–O and CO, respectively. , From the XPS results, it was found that the hydroxyl (−OH) and amino (−NH 2 ) groups exist on the surface of CPDs.…”
Section: Resultsmentioning
confidence: 99%
“…19 Figure 3c shows a high-resolution N 1s spectrum with two peaks, corresponding to pyrrolic N (400.2 eV) and pyridinic N (399.1 eV), respectively. 20,21 Figure 3d shows that the O 1s band contains two peaks at 533.0 and 531.6 eV corresponding to C−O and CO, respectively. 22,23 From the XPS results, it was found that the hydroxyl (−OH) and amino (−NH 2 ) groups exist on the surface of CPDs.…”
Section: Resultsmentioning
confidence: 99%
“…The binding forces between drugs and biological macromolecules mainly include electrostatic forces, hydrogen bonds, hydrophobic forces, and van der Waals forces. , DNA is an anion polyelectrolyte with a phosphate group, which may produce electrostatic interaction with drugs. To investigate whether there was electrostatic force between two kinds of AuNCs and ctDNA, we studied the effects of NaCl and CaCl 2 on the interactions between two kinds of AuNCs and ctDNA.…”
Section: Resultsmentioning
confidence: 99%
“…The binding forces between drugs and biological macromolecules mainly include electrostatic forces, hydrogen bonds, hydrophobic forces, and van der Waals forces. 24,25 DNA is an anion polyelectrolyte with a phosphate group, which may produce electrostatic interaction with drugs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, it is important to prepare an easy-to-obtain, economical, and environmentally friendly functional material for the construction of electrochemical sensors for detecting E. coli O157:H7. As a member of "zero-dimensional" carbon nanomaterials, carbon dots (CDs) have some advantages of good biocompatibility, simple synthesis, and excellent conductivity (Zhang et al, 2019;Huang et al, 2020;Zhang and Du, 2020;He H. et al, 2021;Lin et al, 2021;Xu and Liu, 2021), and they have been successfully used to construct new electrochemical sensors, such as Pd-Au@CDs nanocomposite that we prepared for the preparation of the novel electrochemical DNA biosensor (Huang et al, 2017). Liu et al designed an electrochemical sensor for measuring catechol based on F, N-doped CDs (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%